Effect of Different Phosphorus Modifiers on Microstructure and Properties for Al-Si Alloy. Issue 3 (March 2021) - Hong, Xiaolu; Chen, Dahui; Xu, Ying; Zhu, Honglei; Zhang, Jiang; Liu, Yongqiang; Peng, Yingjiang; Hou, Linchong
Abstract: The coarse primary silicon structure will deteriorate the material properties of Al-Si alloy. It is necessary to optimize the morphology and size of primary silicon through modification, so as to improve the properties of Al-Si alloy. In this paper, four different phosphorus modifiers, AlP4, P-salt, P-Cu and Al-3P, were used to modify the Al-Si alloy. The microstructure and mechanical properties of the modified Al-Si alloy were compared and analyzed.